Assessing infection prevention and control (IPAC) knowledge of tattoo artists of British Columbia - Singh, Jagjeet; BCIT School of Health Sciences, Environmental Health; Heacock, Helen (BCIT Environmental Public Health Journal, 2022)
Tattooing has become very popular in the past 30 years. The prevalence of tattoos has increased such that approximately twenty percent of Canadians have at least one tattoo. The Personal Services Establishments (PSEs) industry in BC lacks stringent regulations. Tattoo studios are a significant part of the PSEs industry. Tattooing includes invasive procedures and as such, has the potential for spreading many types of infections. Proper Infection Prevention and Control (IPAC) procedures are required to minimize the risk of infections. The British Columbia Ministry of Health (MoH) guidelines for PSEs provide direction for IPAC, however, these guidelines are not enforceable by Environmental Health Officers. Therefore, the IPAC knowledge of tattoo artists in the absence of stringent regulations and its relationship with various other factors should be assessed to gauge any deficits in knowledge and identify opportunities for education.